A Novel Liquid Chromatography–Tandem Mass Spectrometry Method to Quantify Tryptophan and Its Major Metabolites in Serum to Support Biomarker Studies in Patients with Cancer Undergoing Immunotherapy - Anna Siemiątkowska; Barbara Kuźnar-Kamińska; Katarzyna Kosicka-Noworzyń; Kamila Nowaczewska; Hanna Winiarska; Dominika Popiołek; Filip Kamiński; Franciszek K. Główka (Molecules)
Tryptophan (TRP) is an essential amino acid crucial for the production of many bioactive compounds. Disturbances in TRP metabolism have been revealed in various diseases, many of which are closely related to the immune system. In recent years, we have focused on finding blood-based biomarkers of successful immunotherapy in cancer. Thus, we aimed to develop a robust liquid chromatography–tandem mass spectrometry (LC-MS/MS) method for TRP and its metabolites that could be used in biomarker studies. Although analyzing TRP derivatives in biological matrices is not a new topic, we encountered multiple challenges during method development. One of them was the phenomenon of cross-interferences between the analyzed molecules, which has not been explored in most published papers. We noticed that injecting a pure single-compound solution often generated a signal in the other compounds’ MS/MS channels. Specifically, TRP generated unexpected peaks in the channel for kynurenine, kynurenic acid, and xanthurenic acid, while kynurenine generated peaks in the channel for kynurenic acid. We also recorded a mutual cross-talk between kynurenine and isotope-labeled TRP. Different origins of the observed cross-signal contribution were proposed. This paper draws attention to investigating cross-interferences in LC-MS/MS, especially when structurally related compounds will be analyzed. Despite all the challenges, the method was successfully validated according to international guidelines (EMA/ICH), and its applicability was confirmed in a pilot study including 20 patients with lung cancer undergoing chemoimmunotherapy.